The Function of Deposits Insurances Institutions to Create a Solid Banking System For The Sake Of Continuity of Infrastructure Development in Indonesia - Prawitra Thalib, - (Primrose Hall Publishing Group, United Kingdom, 2019)
The monetary crisis that hit Indonesia in 1998, which resulted in the liquidation of 16 banks, has made public confidence in the banking sector decreased. To resolve this, the Government has issued a policy giving a guarantee for the entire banks obligations towards its customers, including savings societies (blanket guarantee). Blanket policies guarantee can improve public confidence towards banking, through a solid banking system and trust of the community to the Agency bank, the banking institutions can provide support to project infrastructure in Indonesia, as in any workmanship infrastructure projects definitely need the financial support of banking institutions. In line with this, it is a refinement of the basic rules of the banking system devices, especially in the field of guaranteeing deposits. This refinement aims to create a reliable banking sector and create a healthy banking system, which is efficient and competitive and is expected to be spared from systemic risk and can support infrastructure development in Indonesia.